Synergistic Interactions between Selected β-Lactam Antibiotics and Cinnamic Acid and Its Chosen Derivatives - Tomasz Zawiła; Denis Swolana; Marta Zawiła; Robert D. Wojtyczka (MDPI AG, 2024)
Staphylococcus epidermidis, a component of human microbiota, may also cause life-threatening opportunistic infections. These are becoming increasingly common infections associated with the implantation of various implants. Due to the exhaustion of antibiotic resources, new substances with antimicrobial activity are being sought. The present study examined the antibacterial effect of cinnamic acid and its derivatives and their combinations with β-lactam antibiotics on the growth of Staphylococcus epidermidis strains isolated from vascular infections. The data obtained during the research indicated that cinnamic acid and its derivatives, sinapic acid, ferulic acid, and p-coumaric acid, have weak antibacterial activity (MIC values at the level of 2048 and 4096 mg/L). The combination of cinnamic acid and its derivatives with β-lactam antibiotics increases the effectiveness of their action and may demonstrate various pharmacological effects depending on the established cutoff.